2019
DOI: 10.3847/1538-4357/ab527e
|View full text |Cite
|
Sign up to set email alerts
|

Observational Analysis on the Early Evolution of a CME Flux Rope: Preflare Reconnection and Flux Rope’s Footpoint Drift

Abstract: We study the early evolution of a hot-channel-like magnetic flux rope (MFR) toward eruption. Combining with imaging observation and magnetic field extrapolation, we find that the hot channel possibly originated from a pre-existing seed MFR with a hyperbolic flux tube (HFT). In the precursor phase, three-dimensional tether-cutting reconnection at the HFT is most likely resulting in the heating and buildup of the hot channel. In this process, the forming hot channel was rapidly enlarged at its spatial size and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 125 publications
(160 reference statements)
3
24
0
1
Order By: Relevance
“…The evolutions of the identified footpoint regions are demonstrated in Figure 1 , which present obvious drifting of the flux rope footpoints as mentioned in previous papers. 18 , 39 , 40 , 41 Figure 2 shows the evolution of the toroidal flux during the eruption. It should be mentioned that our method sometimes derives some small and irregular dimming regions that extend from the main dimming region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolutions of the identified footpoint regions are demonstrated in Figure 1 , which present obvious drifting of the flux rope footpoints as mentioned in previous papers. 18 , 39 , 40 , 41 Figure 2 shows the evolution of the toroidal flux during the eruption. It should be mentioned that our method sometimes derives some small and irregular dimming regions that extend from the main dimming region.…”
Section: Resultsmentioning
confidence: 99%
“…Aiming at the drifting of the footpoints of the CME flux rope, Chen et al. 39 used a trial-and-error method to detect the core-dimming region and found that the magnetic flux there (i.e., the toroidal flux) shows a decreasing trend, if the core-dimming region is considered the footpoint region of the CME flux rope. In addition, Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted by theoretical models [35] that if the MFR grows to sufficiently twisted, the hooks of the double-J shaped footprints of the QSL can indeed close onto themselves, becoming two closed rings, although this is not reproduced by the numerical model of [20], possibly because their simulation run is stopped before the MFR grows to such a high degree of twist. Very recently, a few papers reported that there is a systematic decrease of the toroidal flux of erupting MFR after its fast increase (e.g., [40,42,43]). In particular, Xing et al [40] developed a practical method for estimation of the toroidal flux of MFR during eruption by combining twin coronal dimmings and the hooks of flare ribbons.…”
Section: Introductionmentioning
confidence: 99%
“…During eruptive flares, 3D reconnection geometries are more complex than 2D. The photospheric footpoints, for example, are observed to brighten sequentially along the polarity inversion line during the rise phase [158][159][160], as modelled by Priest & Longcope [138] in terms of zipper reconnection ( §3b). Also, Li et al [158] found that one end of an eruptive flux rope is fixed and the other end exhibits apparent slippage along a hook-shaped flare ribbon.…”
Section: (C) Quasi-separator Reconnection: Modelling and Observationsmentioning
confidence: 99%